MIMICRY OF FISH LARVAE LIVE FOOD WITH PARTICLES OBTAINED BY IONIC GELATION AND COATED WITH PROTEINS THROUGH ELECTROSTATIC INTERACTION - TELLO, JULIANA BÜRGER; TELLO, FERNANDO; LEITÃO, NATÁLIA DE JESUS; PORTELLA, MARIA CÉLIA; GROSSO, CARLOS RAIMUNDO FERREIRA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2013)
In an attempt to mimic the proximate composition found in Artemia’s nauplii, a type of food commonly used in intensive rearing of fish larvae, inert diets were produced by ionic gelation using either low methoxyl amidated pectin or sodium alginate and subsequently coated with whey proteins by electrostatic interaction. The particles were morphologically characterized by optical microscopy and scanning electron microscopy, showing spherical shape when moist or rehydrated. The resulting particles were characterized according to their proximate composition, average size, and rehydration behavior after freeze drying. The coated pectin and alginate particles, had sizes averaging 256.7 µm ± 17.1 and 241.9 µm ± 7.5, respectively, with no statistical difference. In relation to the contents of lipid, protein, dry-matter, and ash, the resulting particles were similar to the live food. However, an in vivo evaluation with fish larvae becomes necessary to confirm their suitability and functionality.